Once-daily, subcutaneous vosoritide therapy in children with achondroplasia: a randomised, double-blind, phase 3, placebo-controlled, multicentre trial. Issue 10252 (5th September 2020) - Savarirayan, Ravi; Tofts, Louise; Irving, Melita; Wilcox, William; Bacino, Carlos A; Hoover-Fong, Julie; Ullot Font, Rosendo; Harmatz, Paul; Rutsch, Frank; Bober, Michael B; Polgreen, Lynda E; Ginebreda, Ignacio; et al.
Summary: Background: There are no effective therapies for achondroplasia. An open-label study suggested that vosoritide administration might increase growth velocity in children with achondroplasia. This phase 3 trial was designed to further assess these preliminary findings. Methods: This randomised, double-blind, phase 3, placebo-controlled, multicentre trial compared once-daily subcutaneous administration of vosoritide with placebo in children with achondroplasia. The trial was done in hospitals at 24 sites in seven countries (Australia, Germany, Japan, Spain, Turkey, the USA, and the UK). Eligible patients had a clinical diagnosis of achondroplasia, were ambulatory, had participated for 6 months in a baseline growth study and were aged 5 to less than 18 years at enrolment. Randomisation was done by means of a voice or web-response system, stratified according to sex and Tanner stage. Participants, investigators, and trial sponsor were masked to group assignment. Participants received either vosoritide 15·0 μg/kg or placebo, as allocated, for the duration of the 52-week treatment period administered by daily subcutaneous injections in their homes by trained caregivers. The primary endpoint was change from baseline in mean annualised growth velocity at 52 weeks in treated patients as compared with controls. All randomly assigned patients were included in the efficacy analyses (n=121). All patients who received one dose of vosoritide or placebo (n=121) were included in the safety analyses. The trial is complete and is registered, with EudraCT, number, 2015-003836-11. Findings: All participants were recruited from Dec 12, 2016, to Nov 7, 2018, with 60 assigned to receive vosoritide and 61 to receive placebo. Of 124 patients screened for eligibility, 121 patients were randomly assigned, and 119 patients completed the 52-week trial. The adjusted mean difference in annualised growth velocity between patients in the vosoritide group and placebo group was 1·57 cm/year in favour of vosoritide (95% CI [1·22–1·93]; two-sided p<0·0001). A total of 119 patients had at least one adverse event; vosoritide group, 59 (98%), and placebo group, 60 (98%). None of the serious adverse events were considered to be treatment related and no deaths occurred. Interpretation: Vosoritide is an effective treatment to increase growth in children with achondroplasia. It is not known whether final adult height will be increased, or what the harms of long-term therapy might be. Funding: BioMarin Pharmaceutical.